Moisture dynamics of the cultivated soil layer while soybean cultivation - S. I. Kambulov; Yu. A. Semenikhina; V. B. Rykov; V. V. Kolesnik; A. S. Popov (Зерновое хозяйство России)
Moisture dynamics of the cultivated soil layer while soybean cultivation The article considers the possibilities of agro technical measures to influence on the dynamics of soil moisture. The article presents the study results of the moisture determination in various soil layers in conditions of insufficient and unstable moistening of the south of Russia. The trials were made in the experimental plots of the NCRIMEA (the structural department of the FSBSI ‘ARC ‘Donskoy’, Zernograd of the Rostov region) in the conditions of long-term stationary experiment when cultivating soybean by various technologies (traditional, zero). The moisture content of the soil was taken into account at a depth of 30 and 60 cm using humidity sensors. The measured relative humidity values ranges from 0 to 100%, the accuracy of measurements is ± 3% at a temperature of 250C for a range of 10-90%, beyond this range, the measurement accuracy is ± 5%. To accumulate data, the registration device (a meteostation) ‘Watch Dog 1400 Micro’ was used. The aim of the research was to determine and compare the influence of soil treatment methods on the moisture index in the soil at various levels. The conducted studies established that soil treatment methods had an effect on soil moisture. The average moisture content of the soil on the untreated background is on 23% lower compared to the moisture content of the soil treated by traditional technology. Soil as a dynamic system converts the input signal (the relative humidity of the surrounding air) so that it decreases in magnitude and in the rate of change (dynamism). These features of the soil are determined both by the methods of treatment and by its composition, since the different structure of the soil and its components that determine this structure have different moisture conductivity, moisture capacity, and moisture retention capacity.